Interaksi Sosial dalam Keseharian Masyarakat Plural - Lis Yulianti Siregar (Fakultas Dakwah dan Ilmu Komunikasi, 2021)
Human life is always faced with a variety of diversity, be it skin color, ethnicity, religion, language and so on. With this plurality, it often triggers conflict. To bridge this gap, various kinds of accommodation are needed that can bring these differences together so that there is an understanding and recognition of the existence of a culture. Forms of human interaction with other humans can be associative and dissociative forms. Some of the problems that can produce associative forms of social interaction are ethnocentrism, misunderstanding in values, stereotypes, and prejudice.